PERDA SharÃ®âah antara Legalitas dan Prospek - Mudzakir, Mudzakir (ISLAMICA: Jurnal Studi Keislaman, 2011)
Many have been done to study the problem of SharÃ®âah and other related issues. But little has been done to investigate the notion of the application of SharÃ®âah in Indonesia in the form of regional law, otherwise known as Perda SharÃ®âah. Apart from its importance and sensitivity, the Perda SharÃ®âah is quite ignored by the academic circle in this country. It is toward filling this gap that this paper is written. It is interested first in discussing the nature of Syariah, its values, history, and sources. Then it moves to the currents of thought and modes of interpretation as far as SharÃ®âah is concerned. It finally discusses the ways SharÃ®âah is applied in daily live and how a country like Indonesia âor rather certain districts in it- are involved in formalizing SharÃ®âah as their regional law. The main argument of this paper is that, Islam is not solely about law. Islam is a religion of ethics, morality, belief, and spirituality. Islam is also a way of life, the consequence of which being that it should be comprehended universally as comprehensive system of living. Hence, we argue, that the application of Islam in the form of regional law would mean a simplification of the more universal form of Islam, and a reduction of the more holistic message of the religion.